Energy efficient and high temperature power semiconductors for hybrid electric vehicles - Lau, Cheng Leong. (2010)
The emergence of silicon carbide (SiC) semiconductors having superior properties when compared with silicon (Si) has resulted in significant improvements in the performance of power electronics converter systems. The theoretical benefits of system using SiC power devices are reduction in size and weight and also improvement in efficiency. However, the performances of these SiC devices being implemented in an actual system are not well defined or have been clearly reported. Presently, researches are mostly done on simulation of SiC power devices particularly on diode and the test methodologies and equipment used are not well defined. Therefore, research has to be done in implementing the devices in an actual system and measuring the performance experimentally. In this report, a study is done on a commercial 100W Inverter on its operation and circuit topology. SiC Schottky diodes and JFETs are then retrofitted, replacing the Si diodes and MOSFETs used in the inverter. Efficiency of the inverter and switching characteristics of the power devices is then carried out on the original Inverter and the modified inverter. In addition, a chopper circuit is used to measure losses of Si and SiC devices and to investigate the operation of the SiC devices. The system benefits in using SiC devices is highlighted through the experiment and the results obtained would allow us to find solution to reduction in the size, weight, and the need of the power conditioning and/or thermal management systems in HEVs.